Establishment of Normal Mechanical Tibial Joint Angles in Dachshunds - Banks, Charlotte; Meeson, Richard; Kulendra, Elvin; Carwardine, Darren; Mielke, Benjamin; Pead, Matthew; Phillips, Helen; Phillips, Andrew (Veterinary and Comparative Orthopaedics and Traumatology, 2021)
Objective The aim of this study was to establish breed-standard mechanical tibial joint reference angles in the frontal plane in Dachshunds.Study Design Craniocaudal (n = 38) and mediolateral (n = 32) radiographs of normal tibiae from Dachshunds were retrospectively reviewed. The mechanical medial proximal, mechanical medial distal, mechanical caudal proximal and mechanical cranial distal tibial angles were measured on three occasions by two separate observers using previously established methodology. Interclass correlation coefficient was used to assess the reliability of radiographic measurements.Results The mean and standard deviation for mechanical medial proximal, mechanical medial distal, mechanical caudal proximal and mechanical cranial distal were 93.1 degrees ± 4.2, 97.5 degrees ± 3.9, 75.3 degrees ± 3.7 and 85.0 degrees ± 5.3 respectively. Intra-observer reliability was good to excellent for all measures, while inter-observer reliability was moderate to excellent in the frontal plane and poor to good in the sagittal plane. Dachshund-specific joint reference angles were similar to a range of previously reported non-chondrodystrophic breeds in the frontal plane but differed to most in the sagittal plane.Conclusion Dachshund tibial joint reference angles are reported which can be used in surgical planning for correction of bilateral pes varus.
Keywords: Dachshund; pes varus; joint reference angles; mechanical tibial joint angles; angular limb deformity